A Place at the Table and A Voice in the Hall: "Third Wave" Feminists in the Canadian Academy - Byers, Michele; Crocker, Diane (Atlantis, 2009)
This article discusses the findings of a survey of junior female academics in Canadian universities designed to help describe a cohort we thought would be linked through self-identification or ideology as "third wave" feminists. This work is an exploration of some of the ways junior women academics situate themselves within particular feminist labels and debates about feminism.